EFFECTIVE COMPETENCY BASED SCHOOL MODEL - Indra Prasetia; Akrim Akrim; Emilda Sulasmi (JURNAL TARBIYAH, 2020)
The problem of school performance, especially the performance of personnel involved in school organizations (principals, teachers and staff), is rated lowly. Therefore, the ability of people in school organizations is required to ensure that the school's target will be achieved effectively. This study was conducted by using mixed method (embedded qualitative-quantitative type mix): the qualitative method as the primary method and the quantitative method as secondary method that was carried out in one stage of the study (the qualitative-quantitative stage together). Open and closed questionnaires through predetermined respondents, as well as documentation studies were used as data collection tool. Meanwhile, the data was analyzed by using statistical approach (quantitative) and data transformation (qualitative) was obtained from sources or participants determined in the study. The results showed that from the characteristics of (1) collegiality collaboration skills among teachers, (2) understanding cognitive processes in the administration of teaching, (3) mastery of subject knowledge structures, (4) understanding and appreciation of values, beliefs, and (5) teaching standards, convey direct and positive influence on student and teacher performance. Based on these competency characteristics, teacher and student performance can be predicted, whether effective or not